(untitled) (Cardiovascular Journal, 2021)
A patent foramen ovale (PFO) is highly prevalent in patients with strokes of unknown cause or cryptogenic strokes (CSs). It has been remained an unsolved question as to whether a PFO should be closed or not to prevent recurrent strokes in patients diagnosed with cryptogenic stroke (CS). A paradoxical embolism through a PFO is pointed as a leading cause of CS, especially in younger patients with low risk factors for stroke. It also remains an unsolved matter on type of anti-coagulation therapy, which would be better for patients with CS and a PFO. In addition, surgical and transcutaneous closure of a PFO has been proposed for the secondary prevention of stroke in patients with CS with PFO. Several randomized controlled trials have been conducted in recent years to test whether a PFO closure gives a significant benefit in the management of CS. Many investigators believed that a PFO was an incidental finding in patients with CS. However, meta-analyses and more recent specific trials have eliminated several confounding factors and possible biases and have also emphasized the use of a shunt closure over medical therapy in patients with CS. Therefore, these latest studies can possibly change the treatment paradigm in the near future. We are reporting a case of cryptogenic ischaemic stroke in middle cerebral artery territory due to paradoxical embolism through a PFO which was successfully closed with a device solely by a Bangladeshi Consultant & his team first time in Bangladesh. Cardiovasc. j. 2021; 13(2): 227-234